1993
DOI: 10.1103/physrevb.47.11579
|View full text |Cite
|
Sign up to set email alerts
|

Role of interfacial mixing in giant magnetoresistance

Abstract: We show that the giant magnetoresistance in sputtered Ni-Fe/Cu/Ni-Fe/Fe-Mn spin-valve structures is strongly reduced by the presence of compositionally intermixed regions at the NiFe/Cu interfaces. The ultrathin intermixed layers, which are not ferromagnetic, are centers of strong spin-independent scattering, thus reducing the How of polarized electrons from one ferromagnetic layer to the other. Our results show that interfacial spin-independent scattering must be included in the theory of giant magneto resist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
48
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(49 citation statements)
references
References 17 publications
1
48
0
Order By: Relevance
“…As was discussed in section 8, experiments 79 find that at room temperature there is a substantial reduction in the magnetization of permalloy near the interfaces with copper, which is equivalent to a magnetically-dead layer of 0.2nm thickness. In order to investigate this effect, Oparin et al 80 have performed calculations of the magnetic structure of the intermixed Ni 80 Fe 20 /Cu interfaces.…”
Section: First-principle Modelsmentioning
confidence: 92%
See 2 more Smart Citations
“…As was discussed in section 8, experiments 79 find that at room temperature there is a substantial reduction in the magnetization of permalloy near the interfaces with copper, which is equivalent to a magnetically-dead layer of 0.2nm thickness. In order to investigate this effect, Oparin et al 80 have performed calculations of the magnetic structure of the intermixed Ni 80 Fe 20 /Cu interfaces.…”
Section: First-principle Modelsmentioning
confidence: 92%
“…Furthermore, the Ni moments are much smaller than for pure bulk Ni 80 Fe 20 so the 77 majority channel does not match nearly so well to Cu. Oparin et al 80 conclude that the canting of the Fe moments and a reduction of the magnitude of the Ni moments at the interface is responsible for the measured ''magnetically dead'' layers 79 and result in the strong reduction of GMR. Butler et al 196 found that placing a small amount of Co at the interfaces can dramatically increase the collinearity.…”
Section: First-principle Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies, both theoretical and experimental, have examined the effect of interface morphology on spindependent scattering by measuring the GMR of films with varying degrees of interfacial roughness. [5][6][7][8][9][10][11] Two studies 7,11 find that the GMR increases with increasing roughness, while one 6 finds that the GMR decreases with increasing roughness. Others 8,10 find no influence of roughness, but rather that bulk scattering 8 or crystallographic texture 10 dominates.…”
Section: Introductionmentioning
confidence: 99%
“…For example, NiFe films showed a magnetically dead layer on a NiFe/Cu interface caused by interfacial mixing [10]. (La,Sr)MnO 3 showed a magnetic disorder on a surface, which was probably associated with a structural disorder [11].…”
Section: Introductionmentioning
confidence: 99%